Nephroprotective Effect of Neem Leaves Ethanol Extract on NaCl and Hydrocortisone-Induced Hypertensive Rats - Najwa, Hilya Ummi; Hadi Setya Palupi, Dwi; Herlyanti, Kyky (Jurnal Locus Penelitian dan Pengabdian, 2025)
Kidney failure is one of the main complications of hypertension and has the potential to cause death. Decreased kidney function can be indicated by increased levels of creatinine in the blood. Neem leaves (Azadirachta indica) contain flavonoids, saponins, tannins, phenolics and terpenoids which have antihypertensive and nephroprotective potential. This study used 36 male Wistar rats as test animals. The rats were divided into 6 groups, namely positive control (captopril 25 mg/kgbb), negative control (CMC-Na 0.5%), neem leaf ethanol extract group with doses of 75, 150, 300 mg/kgbb, and normal control. All groups except the normal control were induced with 2.5% NaCl solution (2 ml, p.o.) and 5 mg/kgbb hydrocortisone (s.c.) for 10 days, then given treatment according to each group for 14 days orally. The results of the Kruskal-Wallis test showed significant differences between groups (P <0.05). In the Mann-Whitney test, the neem leaf ethanol extract group with doses of 75, 150 and 300 mg/kgbb compared to the negative control showed significant differences. This proves that all three doses of extract can lower blood pressure and creatinine levels. In the histopathology of the kidneys, there was damage to the tubules and interstitium. In the neem leaf ethanol extract group with a dose of 300 mg/kgbb, there was improvement in the renal tubules and interstitium. Based on these results, it can be concluded that the neem leaf ethanol extract can lower creatinine levels and improve the histopathology of the kidneys in hypertensive rats induced by NaCl and hydrocortisone.